Brazilian multicentre study on preterm birth (EMIP): Prevalence and factors associated with spontaneous preterm birth - Passini, Renato (2014)
Background: Preterm birth rate is increasing and is currently a worldwide concern. The purpose of this study was to estimate the prevalence of preterm birth in a sample of health facilities in Brazil and to identify the main risk factors associated with spontaneous preterm births. Methods and Findings: This was a multicentre cross sectional study on preterm births in 20 referral obstetric hospitals with a case-control component to identify factors associated with spontaneous preterm birth. Surveillance was implemented at all centres to identify preterm births. For eligible consenting women, data were collected through a post-delivery questionnaire completed with information from all mother-newborn medical records until death or discharge or at a maximum of 60 days post-delivery, whichever came first. The risk of spontaneous preterm birth was estimated with OR and 95%CI for several predictors. A non-conditional logistic regression analysis was then performed to identify independently associated factors. The overall prevalence of preterm birth was 12.3%. Among them, 64.6% were spontaneous and 35.4% therapeutic. In the case-control component, 2,682 spontaneous preterm births were compared to a sample of 1,146 term births. Multivariate analyses identified the following as risk factors for spontaneous preterm birth among women with at least one previous birth: a previous preterm birth (ORadj = 3.19, 2.30-4.43), multiple pregnancy (ORadj = 29.06, 8.43-100.2), cervical insufficiency (ORadj = 2.93, 1.07-8.05), foetal malformation (ORadj = 2.63, 1.43-4.85), polyhydramnios (ORadj = 2.30, 1.17-4.54), vaginal bleeding (ORadj = 2.16, 1.50-3.11), and previous abortion (ORadj = 1.39, 1.08-1.78). High BMI (ORadj = 0.94, 0.91-0.97) and weight gain during gestation (ORadj = 0.92, 0.89-0.95) were found to be protective factors. Conclusions: The preterm birth rate in these health facilities in Brazil is high and spontaneous preterm births account for two thirds of them. A better understanding of the factors associated with spontaneous preterm birth is of utmost importance for planning effective measures to reduce the burden of its increasing rates.